2014
DOI: 10.1002/rcm.6893
|View full text |Cite
|
Sign up to set email alerts
|

Identification of multiple constituents from seed of Vaccaria segetalis with an adsorbent‐separation strategy based on liquid chromatography coupled to quadrupole time‐of‐flight mass spectrometry

Abstract: An integrated adsorbent-separation strategy is powerful and reliable for global detection and identification of complex components in herbal prescriptions. The components identified in rat biofluids may also provide helpful chemical information for further pharmacology and active mechanism study on this herb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Therefore, comprehensive identification and quality control of the chemical components in TCMs are important for revealing the therapeutic mechanism and ensuring their safety. However, TCMs are often difficult to identify clearly because hundreds of various chemical constituents are present in these complex systems, and some are at lower concentration levels . So it is very important to develop sensitive and reliable analytical methods for the identification and detection of TCMs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, comprehensive identification and quality control of the chemical components in TCMs are important for revealing the therapeutic mechanism and ensuring their safety. However, TCMs are often difficult to identify clearly because hundreds of various chemical constituents are present in these complex systems, and some are at lower concentration levels . So it is very important to develop sensitive and reliable analytical methods for the identification and detection of TCMs …”
Section: Introductionmentioning
confidence: 99%
“…However, TCMs are often difficult to identify clearly because hundreds of various chemical constituents are present in these complex systems, and some are at lower concentration levels. [5] So it is very important to develop sensitive and reliable analytical methods for the identification and detection of TCMs. [6] In recent years, LC-MS-based techniques with excellent sensitivity and specificity have been proven to be powerful approach to simultaneously characterize and determine the different constituents in TCM researches.…”
Section: Introductionmentioning
confidence: 99%
“…The seed of this plant is used for the promotion of diuresis and milk secretion, activation of blood circulation and the relief of carbuncle. Some compounds were separated from Vaccaria segetalis (Qi et al 2014;Wang et al 2011), but to date the active compound has still not been known, and there are few reports on the lactogenic mechanism of Vaccaria segetalis. In our previous reports, we found that Vaccaria segetalis promotes lactogenesis by enhancing JAK-STAT5 and mTOR pathways in dairy cow mammary epithelial cells (DCMECs) Tong et al 2011), but how Vaccaria segetalis excerts its role is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…1) is a novel cyclic hexapeptide [cyclo-(Gly-Val-Pro-Val-Trp-Ala)] and a chief cyclic peptide component of V. segetalis seeds . According to the literature, very few analytical methods have been reported for the analysis of segetalin A in V. segetalis (Wang et al, 2011;Dong et al, 2012;Qi et al, 2014). The first method involved a high-speed countercurrent chromatography to separate cyclic peptides from the seeds of V. segetalis (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A conventional HPLC-PDA method was employed to assay segetalin A in the plant using a mobile phase of acetonitrile-water with gradient elution (Dong et al, 2012). The third method involved liquid chromatography/quadrupole time-of-flight tandem mass spectrometry (LC/QTOF-MS/MS) to identify the multiple constituents of V. segetalis (Qi et al, 2014). Recently, LC/QTOF-MS/MS has been investigated for the in vivo metabolism and tissue distribution of V. segetalis containing segetalin A (Qi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%